Turkey hen sperm storage tubule transcriptome response to artificial insemination and the presence of semen - Brady, Kristen; Krasnec, Katina; Hanlon, Charlene; Long, Julie A. (Frontiers in Physiology, 2024)
Sperm storage within the uterovaginal junction (UVJ) of avian species occurs in specialized structures termed sperm storage tubules (SSTs) and allows for prolonged storage of semen, though the molecular mechanisms involved in semen preservation are not well understood. Little work has been done examining how function of the SSTs is impacted by insemination and by semen present in the SSTs. Transcriptome analysis was performed on isolated SSTs from turkey hens receiving no insemination (control), sham-insemination, or semen-insemination at three timepoints (D1, D30, and D90 post-insemination). Bioinformatic and functional annotation analyses were performed using CLC Genomics Workbench, Database for Annotation, Visualization, and Integrated Discovery (DAVID), and Ingenuity Pathway Analysis (IPA). Pairwise comparisons and k-medoids cluster analysis were utilized to decipher differential expression profiles in the treatment groups. The SST transcriptome of the semen-inseminated group exhibited the greatest differences within the group, with differences detectable for up to 90 days post-insemination, while control and sham-inseminated groups were more similar. In the semen-inseminated samples, upregulation of pathways relating to classical and non-classical reproductive signaling, cytoskeletal remodeling, physiological parameters of the local UVJ environment, and cellular metabolism was observed. In the sham-inseminated samples, upregulation of immune pathways and non-reproductive endocrine hormones was observed. This work provides insights into the molecular-level changes of the SST in response to insemination as well as to the presence of semen. Results from this study may have direct implications on fertility rates as well as potential strategies for avian semen cryopreservation protocols.